Taxonomische Analyse als Mittel zum Aufbau eines natürlichen Systems. - Smirnov, Eugen (Contributions to Entomology = Beiträge zur Entomologie, 1968)
The author defends his own position in the Held of "exact systematization" which is characterized by the use of mathematical methods for the formation of a natural system of organisms. Unlike many scientists who advocate the principle of the equivalence of the characteristics the author emphasizes the necessity of "weighing" the characteristics as to their frequency in the taxon under consideration. The present paper explains the general conception of the taxonomical analysis suggested by the author. He replies to the criticism of his views expressed by Sokal and Sneath (1963) and gives his ideas about the relations between the natural system and phylogeny.